KONTRADIKSI HUKUMAN MATI DI INDONESIA DIPANDANG DARI ASPEK HAK ASASI MANUSIA, AGAMA DAN PARA AHLI HUKUM - Atet Sumanto (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2004)
In pro party opinion, death sentence as the criminal sanction at ultimum remedium, still should be carried out for extreme crime, while as the opposite party the death of human being is beyond mankind rights.